2021
DOI: 10.1111/jocs.15610
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and depression in cardiac surgery: A comprehensive review of risk factors, pathophysiology, and management

Abstract: Background Mental health and wellbeing continue to gain more attention as they are inextricably associated with clinical outcomes, particularly quality of life. Many medical ailments and major surgeries affect patients’ mental health, including depression and delirium. Aims The objective of this manuscript was to comprehensively review and critically examine the literature pertaining to cardiac surgery, depression, and delirium. Methods This is a narrative review article. We performed our search analysis by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 207 publications
(648 reference statements)
0
10
0
2
Order By: Relevance
“…The exact mechanism of post-cardiac surgery delirium is uncertain and may be of multifactorial origin ( 50 ). But Previous studies have suggested that old age ( 51 ) and inflammation ( 52 ) are independent risk factors for POD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism of post-cardiac surgery delirium is uncertain and may be of multifactorial origin ( 50 ). But Previous studies have suggested that old age ( 51 ) and inflammation ( 52 ) are independent risk factors for POD.…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing cardiac surgery, the incidence of delirium is strongly associated with the duration of mechanical ventilation, ICU stay, and hospitalization. POD can prolong the mechanical ventilation time, length of ICU stay, length of hospitalization after cardiac surgery ( 50 , 63 , 64 ), and duration of mechanical ventilation, length of ICU stay, and length of hospitalization serve as precipitating factors for POD ( 65 , 66 ). However, our meta-analysis did not show a significant difference in the aforementioned clinical outcomes based on the premise that melatonin can significantly reduce the incidence of POD.…”
Section: Discussionmentioning
confidence: 99%
“…69 Female sex, lower levels of education, and lack of social support are predictors of depression. 69 Pre-existing depression can be associated with increased mortality and morbidity after cardiac surgery. 70 Increased cardiac events, prolonged recovery, impaired quality of life after recovery, and increased readmissions have been correlated with depression.…”
Section: Depressionmentioning
confidence: 99%
“…An aging population will continue to contribute to a greater prevalence of heart disease in an older and increasingly frail cardiac patient population, who are themselves vulnerable to delirium. The perioperative team should view the occurrence of postoperative delirium as a quality indicator for health care delivery because it is common, associated with iatrogenesis and integrally linked to processes of care (Fatehi Hassanabad et al 2021 ). The contemporary cardiac team should seek to incorporate routine risk identification during the preoperative evaluation and consider opportunities to optimize vulnerable patients while they await surgery (Enomoto et al 2021 ).…”
Section: Main Textmentioning
confidence: 99%